Unionization Versus Corporate Welfare: The "Dofasco Way" - Storey, Robert (Labour / Le Travail, 1983)
This article examines the contest between the United Steelworkers of America and management at Dominion Foundries and Steel (Dofasco) for the loyalty of Dofasco workers. Situated in the 1930s and 1940s during the rise and consolidation of industrial unionism in Canada, the article traces the development at Dofasco of a corporate welfare, human relations approach to management that effectively challenged and ultimately defeated the drive for unionization. At the same time Dofasco pursued a consistent and oftentimes ruthless policy of dismissing union organizers and activists from within its workforce. Both strategies combined to produce what this paper terms the "Dofasco Way." The centrepiece of the "Dofasco Way" was the successful operation of a profit-sharing Fund. For only the profit-sharing Fund brought together both elements of the "Dofasco Way": loyalty and fear among the workers. Loyalty was created because the Fund provided security. Fear was created through threats to terminate the Fund should the company ever be organized. In the end, however, it was the programmes designed to produce loyalty that led to the Dofasco workers' rejection of unionism.